PENGARUH PEMAHAMAN WRITING MATHEMATICS MAHASISWA DALAM MENGKOMUNIKASIKAN SUATU BUKTI PERNYATAAN DALAM MATEMATIKA - Intan Nisfulaila (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
The ability of writing and communicating Mathematics text are needed to get the whole understanding of specific topic in Mathematics. But so far, it is still can be found some meaningless statement that implies some misconceptions. The qualitative data analysis is conducted in this research to find out how big the change of the writing mathematics skill after conducting a technical guidance. The result of data analysis and some evaluation show that the skill of understanding the concept of writing mathematics takes effect in communicating or creating a proof of mathematical statement.